KEPUASAN KERJA KARYAWAN: PERSPEKTIF LEADER MEMBER EXCHANGE DAN ORGANIZATIONAL JUSTICE - Ali Jufri; Puspa Dewi Yulianty; Sari Laelatul Qodriah; Imam Hadiwibowo (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The role of justice plays an important function in shaping the behavior and perceptions of employees about the organization. Being interested in observing organizational justice is a key model and can act as a basic source of results for employees and organizations developing ideal relationships and building shared job satisfaction between employees and employers in PD. Sumber Utama Ciperna. This research is a type of casual research with a quantitative approach and uses a questionnaire instrument by taking a sample of 66 employees which means it is a saturated sample. This research shows that leader member exchange has a positive and significant effect on employee job satisfaction because there is a relationship between superiors and subordinates that is quite harmonious, communication is established between superiors and good subordinates, there is also a relationship of mutual trust given by superiors to their subordinates and the involvement of superiors in defending their employees in front of other superiors. Organizational justice partially has a significant influence on employee job satisfaction. Leader member exchange and Organizational justice simultaneously have a significant influence on employee job satisfaction. Keywords: LMX, Organizational Justice, Employee Job Satisfaction